Penerapan Inovasi Jus Kacang Hijau dan Jambu Biji untuk Meningkatan Kadar Hemoglobin pada Ibu Hamil Anemia Trimester III di PMB Umi Muntamah - Susanti, Tria; Sulastri, Eti (Prosiding University Research Colloquium, 2019)
Implementing the application of green bean juice and guava in pregnant women with anemia TM III at Umi Muntamah Sruweng PMB. This study was descriptive analytic, with a case study approached. Data were obtained through direct observation. Result: after being given participants’ green bean juice and red guava juice for 14 days, there was an increase in Hemoglobin, ie 10.7g / dL to 13 g / dL (participant 1), 8.5 g / dL to 12.2 g/dL( participant 2), 9.6 g / to 12.1 g / dL (participant 3), 8.6 g / dL to 11.7, and 9.7 g / dL to 12.2 g / dl. Giving green bean juice and guava juice have been applied by the five participants, it was given in the afternoon and evening as a companion fe tablet in 14 days. The five participants experienced an increase in HB levels from anemia to not be anemic. There was a change in Hemoglobin levels after consuming green bean juice and red guava juice that the mother with anemia became not anamic.